Plant Diversity in Different Land Use Types at The Peat Hidrological Unit (PHU) of Mendahara – Batanghari River, Jambi Province - Aji Nuralam Dwisutono; Sri Wilarso Budi; Istomo Istomo (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
The characteristics of tropical peatlands are still able to form a high diversity of plants. Conversion of tropical peatlands affects the composition of plants. The aim of this study was to find out effect of land use changes to the composition and diversity of plants in the Peat Hydrological Unit (PHU) Mendahara - Batanghari River. The research was conducted in three land use categories, namely secondary forest, coffee plantation, and oil palm plantation (subdivided into oil palm plantation 1 and oil palm plantation 2). In each study location, sample lane 20 m x 200 m were made. Overall, we found 77 species of plants. The results showed number of plant species decreased due to changes of land use. There are 51 - 53 species of plants in secondary forest areas (out of a total of 58 species) that are not found in oil palm and coffee plantations areas. Differences in composition were also shown in the low value of community similarity (<50%). In the oil palm and coffee plantation areas, plant communities tend to be dominated by pioneer plants such as Melicope lunu-ankenda, Coffea liberica, Macaranga triloba, and Melastoma malabathricum. Secondary forest was dominated by plants species that characterize peatlands such as Tetramerista glabra, Parastemon urophyllus, Knema percoriacea, Litsea costalis var. nidularis and Madhuca motleyana. Changes in land use also reduce the level of diversity (H 'and R) at various levels of growth. Whereas in the oil palm and coffee plantation areas tend to form uniform stands (indicated through index E which describes the abundance distribution in community and index C which describes the dominance of species). Generally, the distribution pattern of plants is clumped. Uniform distribution was found in K. percoriacea and L. costalis var. nidularis. Keywords: land use changes, peatland characteristics, plant composition, plant diversity